2020
DOI: 10.2334/josnusd.20-0195
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of single crown restorations fabricated with resin-based CAD/CAM materials

Abstract: Computer-aided design/computer-aided manufacturing (CAD/ CAM) restorative materials have been widely used owing to a number of advantages, including stable quality of the materials, lower costs, and time-saving factors. Resin-based CAD/CAM materials for definitive restorations are classified into two groups: dispersed nanoparticle-filled composite resin and polymer-infiltrated-ceramic-network materials. Resinbased CAD/CAM materials have been applied to single crown restorations as a monolithic structure for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This suggests that the access hole may be resistant to tensile stresses. Conversely, it is known that composite resin restorations are vulnerable to the oral environment and susceptible to occlusal wear and deterioration 26) . Therefore, additional research should be conducted to determine the durability of the CAD/CAM composite resin restorations for HACs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the access hole may be resistant to tensile stresses. Conversely, it is known that composite resin restorations are vulnerable to the oral environment and susceptible to occlusal wear and deterioration 26) . Therefore, additional research should be conducted to determine the durability of the CAD/CAM composite resin restorations for HACs.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the brand of the CAD/CAM resin block was not incorporated as a covariate because all products met certain flexural strength criteria of the material product regulation. In fact, a recent literature review has shown that the type of the commercially available CAD/CAM resin block materials does not influence the survival rate of CAD/CAM composite crown treatments [ 9 ]. In both models, there were no significant differences in the HR with respect to crown placement location.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, compared to premolars, molars are assumed to have several mechanical disadvantages as a result of the greater occlusal force applied during biting and the anatomically lower crown height. Several clinical studies have reported the clinical outcomes of CAD/CAM composite crowns [ 9 11 ]. For example, Miura et al published the results of a large retrospective study, reporting that the success and survival rates of CAD/CAM composite crowns applied to the premolar region were 71.7% and 96.4%, respectively, over three years [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abutment and antagonist teeth included in this study were single teeth. Previous studies investigated the survival rate of single crowns or teeth [25][26][27][28] and these results might be applied to the reasons for failed teeth including the abutment and antagonist teeth. Above all, a report by Goodacre et al reported the most common complications of single crowns, and these included endodontic disease, porcelain fracture, loss of retention, periodontal disease and caries [25].…”
Section: Discussionmentioning
confidence: 99%